Role of Metals in Neuronal Apoptosis: Challenges Associated with Neurodegeneration - Bharathi; Ravid, R.; Jagannathan Rao, K. S. (Current Alzheimer Research, 2006)
Apoptosis is a tightly controlled process in which cell death is executed through activation of specific signalling pathways. Within cells, there are positive and negative regulatory pathways of apoptosis, hence it is targeted as ‘Double- edged sword’, the balance between these pathways dictates the cell fate. The past decade has seen intense focus on the mechanisms of apoptosis. Many important observations on the various signalling pathways mediating apoptotic cell death have been made and our understanding of the importance of apoptosis in both normal growth and development and pathophysiology has greatly increased. In addition, mechanisms of metal-induced toxicity continue to be of interest given the ubiquitous nature of these contaminants. The purpose of this review is to summarize our current understanding of the apoptotic pathways that are initiated by metals in Alzheimer's disease. Increased understanding of metal-induced (direct) and metal-amyloid-β (indirect) linked neuronal cell death through the formation of reactive oxygen species (ROS) is critical to illuminate mechanisms of metal-induced cell death, as well as the potential role of metal speciation in neurodegeneration.
Keywords: reactive oxygen species